Legal framework regulating for improving accessibility to built environment for disabled persons in Malaysia - Maidin, Ainul Jaria (2012)
Accessibility of the built environment is a key factor in people with disabilities achieving greater independence, participation and social inclusion. An inaccessible built environment affects all members of society. However, for people with disabilities, the barriers to equal participation in society due to an inaccessible environment are much greater. This article analyses the legal framework regulating creation of accessibility to the built environment for disabled persons in Malaysia to overcome the challenges with respect to participation in societal activities.